The past, the present, and the foreseeable future of Russian manufacturing subsidiaries of Western multinational corporations. Issue 2 (July 2021) - Gurkov, Igor; Saidov, Zokirzhon
This article retraces the development of Russian manufacturing subsidiaries of Western multinational corporations from the late 1980s until 2019. Using secondary sources and a unique handcrafted database on significant extensions of manufacturing facilities of Western multinational corporations in Russia during 2012–2018, we present the position of Russian manufacturing subsidiaries of Western multinational corporations before and after the beginning of sanctions. We also indicate the major strategic challenges that they currently face, including the necessity to maintain dual loyalty (to home country and host country authorities), manage the deteriorating quality of business regulations in Russia, and overcome the increasing shortage of qualified personnel at all levels. The data on the opening of new facilities in 2017–2018 reveal that such issues impede but cannot stop the quantitative development of foreign-owned Russian manufacturing facilities. At the same time, saving on managerial expenses and low "investments in non-current assets" of the established manufacturing subsidiaries may break down "the innovation engine" assembled in many Russian manufacturing subsidiaries of Western multinational corporations and bring them into the periphery of their corporate parents, where the attention and resources from the corporate center are lacking.